A positive electrode material, a positive electrode sheet, a secondary battery, and an electric device
Patent Information
- Application Number
- CN202611240172.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-09
AI Technical Summary
但该类电池存在能量密度偏低的固有短板,难以适配长续航车型的发展需求,在很大程度上限制了电动汽车续航里程的进一步提升
[0016]本申请提供的正极材料,通过构建不同粒径颗粒级配的磷酸铁锂颗粒,并对各级颗粒的碳包覆层厚度进行差异化调控设计,在有效提升材料压实密度的基础上,可显著增强其电子导电性能,进而实现正极材料能量密度与动力学性能的协同优化。
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This application relates to the field of cathode material technology, and in particular to a cathode material, cathode sheet, secondary battery and electrical equipment. Background Technology
[0002] In the field of new energy vehicles, lithium iron phosphate batteries have become the mainstream choice for power batteries and are widely used due to their excellent safety, low cost, and ultra-long cycle life. However, this type of battery has an inherent weakness of low energy density, making it difficult to meet the development needs of long-range vehicles and greatly limiting the further improvement of the driving range of electric vehicles.
[0003] Traditional lithium iron phosphate cathode materials rely solely on increasing particle size to improve compaction density, which is insufficient to significantly enhance battery energy density. Existing research often employs methods that introduce small-diameter particles to fill the gaps between large particles. While this improved method can effectively increase compaction density compared to traditional single-particle systems, it still falls short of meeting the performance requirements of current applications. Furthermore, uneven lithium-ion insertion / extraction during charge and discharge can easily occur, leading to localized polarization effects and ultimately degrading the kinetic performance of the secondary battery.
[0004] Therefore, how to synergistically improve the energy density and kinetic performance of lithium iron phosphate materials has become a key technical challenge in the research and development of lithium iron phosphate batteries. Summary of the Invention
[0005] This application provides a cathode material that, through differentiated design of particle size distribution and carbon coating thickness, provides a cathode material basis for high-performance cathode sheets with high real density and kinetic performance.
[0006] This application also provides a positive electrode sheet with excellent energy density and kinetic performance, which can provide solid material support for improving the rate performance and energy density of secondary batteries.
[0007] This application also provides a secondary battery that has both excellent energy density and rate performance, and can be widely used in a variety of fields with stringent battery performance requirements.
[0008] This application also provides an electrical device that can achieve efficient and long-lasting operation by relying on the stable energy supply and efficient charging and discharging characteristics of the aforementioned secondary battery, effectively improving the battery life and user experience of the electrical device, and has a wide range of application scenarios.
[0009] In a first aspect, embodiments of this application provide a cathode material, the cathode material comprising lithium iron phosphate, the lithium iron phosphate comprising a first particle and a second particle, the first particle having a particle size of D1, D1 being 20~100nm, and the second particle having a particle size of D2, D2 being 1~4μm;
[0010] The first particle includes a first lithium iron phosphate matrix and a first carbon coating layer disposed on at least a portion of the surface of the first lithium iron phosphate matrix, wherein the thickness of the first carbon coating layer is h1, and h1 is 0.0025~0.025μm;
[0011] The second particle includes a second lithium iron phosphate matrix and a second carbon coating layer disposed on at least a portion of the surface of the second lithium iron phosphate matrix, wherein the thickness of the first carbon coating layer is h2, and h2 is 0.001~0.015μm;
[0012] The cathode material satisfies: 1
[0013] Secondly, embodiments of this application provide a positive electrode sheet, the positive electrode sheet comprising the aforementioned positive electrode material; the porosity of the positive electrode sheet is 10~40%.
[0014] Thirdly, embodiments of this application provide a secondary battery, the secondary battery including the positive electrode plate.
[0015] Fourthly, embodiments of this application provide an electrical device including the aforementioned secondary battery.
[0016] The cathode material provided in this application, by constructing lithium iron phosphate particles with different particle size distributions and by differentially controlling the thickness of the carbon coating layer of each particle, can significantly enhance its electronic conductivity while effectively improving the compaction density of the material, thereby achieving synergistic optimization of the energy density and kinetic performance of the cathode material. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0018] To improve the energy density of lithium iron phosphate (LFP) batteries, existing technologies typically employ a multi-level particle gradation system to optimize the electrode microstructure. Small particles fill the gaps between larger particles to increase electrode compaction density, thereby enhancing battery energy density. The inventors analyzed that the lithium-ion solid-phase transport paths differ significantly among particles of different sizes, and smaller particles are more sensitive to adjustments in carbon coating thickness, while larger particles are less affected by carbon layer thickness. Existing technologies use a uniform carbon coating thickness for particles of different sizes, making it difficult to simultaneously ensure both effective gap filling by small particles and balanced lithium-ion transport between particles. This can easily lead to insufficient conductivity or degraded filling effect, failing to solve the technical challenge of inconsistent lithium-ion transport in multi-level particle systems. Therefore, this invention proposes a differentiated design of the carbon coating thickness for LFP particles of different sizes, constructing an electron-ion synergistic transport mechanism to ultimately achieve synergistic optimization of battery energy density and kinetic performance.
[0019] Based on this, the first aspect of the present invention proposes a cathode material, the cathode material including lithium iron phosphate, the lithium iron phosphate including a first particle and a second particle, the particle size of the first particle being D1, where D1 is 0.02~0.1μm, and the particle size of the second particle being D2, where D2 is 1~4μm.
[0020] The first particle includes a first lithium iron phosphate substrate and a first carbon coating layer disposed on at least a portion of the surface of the first lithium iron phosphate substrate, wherein the thickness of the first carbon coating layer is h1, and h1 is 0.0025~0.025μm;
[0021] The second particle includes a second lithium iron phosphate matrix and a second carbon coating layer disposed on at least a portion of the surface of the second lithium iron phosphate matrix, wherein the thickness of the second carbon coating layer is h2, and h2 is 0.001~0.015μm;
[0022] The cathode material satisfies: 1
[0023] The cathode material of the present invention significantly improves the conductivity of the cathode material by constructing a particle-filled system consisting of a first particle and a second particle and controlling the thickness relationship of the particle carbon coating layer, thereby optimizing the compaction density of the cathode material and achieving synergistic optimization of the energy density and kinetic performance of the secondary battery.
[0024] Specifically, the cathode material includes lithium iron phosphate (LFP), which comprises first particles and second particles. The second particles, with a diameter of 1–4 μm, form the main framework structure of the LFP material, while the nanoscale first particles, with a diameter of 0.02–0.1 μm, fill the gaps between the second particles, forming a secondary close-packed structure. This significantly improves the compaction density of the LFP, thereby increasing the energy density of the secondary battery. It should be noted that the particle size refers to the average particle size calculated using SEM imaging.
[0025] Due to the influence of particle size, the lithium-ion solid-phase transport path varies, causing uneven lithium insertion / extraction during cycling of lithium iron phosphate materials, increasing internal impedance, and affecting the kinetic performance of the cathode material. Therefore, based on the two-stage particle gradation, the inventors further introduced carbon coating layers into the first and second particles respectively.
[0026] Specifically, the first particle comprises a first lithium iron phosphate substrate and a first carbon coating layer covering at least a portion of its surface, the thickness h1 of which is 0.0025~0.025 μm. The second particle comprises a second lithium iron phosphate substrate and a second carbon coating layer covering at least a portion of its surface, the thickness h2 of which is 0.001~0.015 μm. By separately setting the first and second carbon coating layers, a continuous conductive network can be constructed on the surfaces of the first and second lithium iron phosphate substrates, effectively improving the electronic conductivity of the lithium iron phosphate material and thus optimizing the kinetic performance of the cathode material. The first particle is a nanoscale particle with a high specific surface area. The first carbon coating layer forms a physical barrier, effectively reducing the degree of side reactions between the first particle and the electrolyte, thereby reducing irreversible loss of active lithium and improving the capacity retention rate of the secondary battery. Simultaneously, the first carbon coating layer effectively prevents the first particle from agglomerating, allowing it to uniformly disperse and fill the second particle, significantly increasing the compaction density of the material. In addition, the first and second carbon coating layers can act as buffer materials to disperse the charging and discharging stress generated during battery cycling, enhance the structural stability of the material, reduce the shedding of positive electrode powder during cycling, and improve the cycle life of the secondary battery.
[0027] Specifically, by precisely controlling h1 to be 0.0025~0.025μm, on the one hand, the size of the first particle can be controlled, thereby optimizing the filling effect of the nano-sized first particle on the gap of the micron-sized second particle, and further improving the compaction density of the lithium iron phosphate material; on the other hand, the first carbon coating layer in this thickness range can construct a more continuous three-dimensional conductive network, while optimizing the migration path length of lithium ions, realizing the simultaneous optimization of the electronic conduction and ion insertion / extraction performance of the first particle, thereby significantly enhancing the kinetic performance of the cathode material.
[0028] It should be noted that h1 can be adjusted by controlling the number of milling processes and the frequency of the classifying wheel in the crushing and deagglomeration process.
[0029] By precisely controlling h2 to a thickness of 0.001~0.015μm, the particle size of the second carbon coating layer within this thickness range can be adjusted, thereby optimizing the matching degree between the first and second particles and achieving optimization of the compaction density of the cathode material. Simultaneously, this thickness range can maintain the continuity of the conductive network on the surface of the second particles, optimizing the lithium-ion transport rate of the second particles.
[0030] It should be noted that h2 can be controlled by adjusting the sintering time of the second high-temperature sintering treatment and the amount of carbon source used.
[0031] Furthermore, by adjusting the ratio of the thickness h1 of the first carbon coating layer to the thickness h2 of the second carbon coating layer to satisfy 1
[0032] It should be noted that the first and second particles include doping elements. The lithium iron phosphate material incorporates at least one doping element selected from Ti, V, Mn, Na, Cr, Mg, Co, Al, Zr, Nb, and Ni. The iron or lithium in the lithium iron phosphate lattice is replaced by ions of the doping element with a larger radius, thereby widening the lithium-ion diffusion channels and introducing lattice defects, reducing the lithium-ion migration barrier, and maintaining the continuity and unobstructedness of the diffusion channels, thus optimizing the rate performance of the secondary battery. Simultaneously, the doping element ions can strengthen the bonding strength of the Fe-O and PO framework within the lithium iron phosphate material, stabilize its olivine crystal structure, reduce structural distortion and internal stress caused by lattice volume changes during charging and discharging, improve the structural stability of the material, and thus optimize the cycle life of the secondary battery.
[0033] It should be noted that the present invention does not specifically limit the preparation method of lithium iron phosphate material. For example, the first particle and the second particle can be prepared separately, and then the first particle and the second particle can be mechanically mixed at a stirring speed of 1500~4000 rpm for 8~15 min.
[0034] The method for preparing the first particle according to the present invention may include the following steps:
[0035] 1) The lithium source, iron source, phosphorus source and solvent are mixed to obtain the first particle mixed slurry;
[0036] 2) The first particle mixture slurry is subjected to a hydrothermal reaction to obtain lithium iron phosphate powder;
[0037] 3) Lithium iron phosphate powder is mixed with carbon source, dopant and solvent to obtain the first particle mixed slurry 2;
[0038] 4) The first particle mixed slurry 2 is subjected to sand milling to obtain the first particle slurry (D50 particle size is 100~300nm).
[0039] 5) The first granular slurry is spray-dried to obtain the first granular raw meal (D50 particle size is 20~60μm);
[0040] 6) The first raw material particle is subjected to a first high-temperature sintering treatment to obtain the first sintered material particle;
[0041] 7) The first sintered material is crushed and deagglomerated to obtain the first particle.
[0042] The method for preparing the second particle may include the following steps:
[0043] 1) The second iron phosphate, lithium source, carbon source, dopant, and solvent are mixed and dispersed to obtain the second particulate slurry;
[0044] 2) The second particle mixture is subjected to sand milling to obtain a second particle mixture (D50 particle size is 200~800nm).
[0045] 3) The second granular slurry is spray-dried to obtain the second granular raw meal (D50 particle size is 20~60μm);
[0046] 4) The second raw material is subjected to a second high-temperature sintering treatment to obtain the second sintered material.
[0047] 5) The second sintered material is crushed and deagglomerated to obtain the second sintered material.
[0048] It should be noted that the present invention does not limit the specific type of lithium source, including but not limited to at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium nitrate, and lithium acetate; the present invention does not limit the specific type of iron source, including but not limited to at least one of ferrous oxalate, ferric phosphate, ferric nitrate, ferrous sulfate, ferric oxide, and magnetite; the present invention does not limit the specific type of phosphorus source, including but not limited to at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, ferric phosphate, and lithium dihydrogen phosphate; the present invention does not limit the specific type of carbon source, including but not limited to at least one of glucose, sucrose, citric acid, polyvinyl alcohol, polyethylene glycol, and starch; the present invention does not limit the specific type of dopant, including but not limited to at least one of compounds of Ti, V, Mn, Na, Cr, Mg, Co, Al, Zr, Nb, and Ni; the present invention does not limit the specific type of solvent, including but not limited to at least one of water, ethanol, and isopropanol.
[0049] It should be noted that the Fe / P ratio of the second ferric phosphate is 0.96~1.
[0050] It should be noted that in the first particle mixed slurry, the mass ratio of lithium source, iron source, phosphorus source and solvent is (16~17):(95~110):(40~50):(350~400); and the mass ratio of lithium iron phosphate powder, carbon source, dopant and solvent in the first particle mixed slurry is 100:(4~10):(3~15):(0.2~1.5):(230~280).
[0051] In the second particle mixed slurry, the mass ratio of second iron phosphate, lithium source, carbon source, dopant and solvent is 1000:(248~255):(5~25):(4~22):(2285~2367).
[0052] It should be noted that the hydrothermal reaction temperature is 150~250℃ and the reaction time is 6~12h;
[0053] The number of sand milling cycles is 2 to 20, the sand milling speed is 500 to 3000 rpm, and the sand milling time is 0.5 to 3 hours each time.
[0054] The inlet air temperature for spray drying is 180~220℃, and the feed rate is 25~70m / s. 3 / h; outlet air temperature 80~100℃;
[0055] The pulverizing pressure for the pulverizing and deagglomeration process is 300~500mPa; the grading frequency is 30~80Hz.
[0056] It should be noted that the gas atmosphere for high-temperature sintering includes at least one of inert gases and reducing gases. Inert gases include, but are not limited to, at least one of helium, neon, argon, and krypton; reducing gases include, but are not limited to, at least one of hydrogen and carbon monoxide.
[0057] The first high-temperature sintering treatment involves a sintering temperature of 650~750℃ and a sintering time of 6~12 hours. The second high-temperature sintering treatment involves a sintering temperature of 680~860℃ and a sintering time of 4~20 hours.
[0058] It is understood that, in addition to lithium iron phosphate, the cathode material also includes binders and conductive agents. This invention does not limit the specific type of binder, but includes, but is not limited to, at least one of polytetrafluoroethylene, polyvinylidene fluoride (PVDF), polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, sodium carboxymethyl cellulose (CMC), hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane. This invention also does not limit the specific type of binder, but includes, but is not limited to, at least one of carbon black (SP), acetylene black, graphene, Ketjen black, and carbon fiber.
[0059] The cathode material of this invention improves material density and optimizes energy density by constructing lithium iron phosphate particles with different particle size distributions. Nanoscale particles fill the gaps between micron-sized particles, increasing material compactness. Furthermore, the carbon coating thickness of each particle size is differentially controlled. This difference in carbon coating thickness compensates for differences in lithium-ion transport paths caused by particle size variations, mitigating the polarization effect caused by uneven lithium insertion / extraction and improving kinetic performance. The cathode material of this invention significantly enhances electronic conductivity while effectively increasing material compaction density, thereby achieving synergistic optimization of energy density and kinetic performance.
[0060] To further optimize the overall performance of the cathode material, in one specific implementation, the value of h1 / h2 ranges from 1.4 to 3.3. When the value of h1 / h2 is in the range of 1.4 to 3.3, the energy density and kinetic performance of the cathode material reach a better level.
[0061] In one specific implementation, h1 ranges from 0.004 to 0.01 μm. Within this range, the compaction density and kinetic properties of the cathode material are further improved, thereby optimizing the energy density and rate performance of the battery.
[0062] In one specific implementation, h2 ranges from 0.003 to 0.007 μm. Within this range, the compaction density and ion transport rate of the cathode material are further improved, thereby optimizing the energy density and rate performance of the battery.
[0063] In one specific embodiment, the average diameter of the first lithium iron phosphate substrate is d1, and the value of d1 ranges from 0.01 to 0.092 μm.
[0064] By precisely controlling the value of d1 within the range of 0.01~0.092μm, the solid-phase diffusion path of lithium ions within the first particle can be effectively optimized, reducing interfacial transport impedance and improving the kinetic performance of the cathode material. This, in turn, optimizes the rate performance of the secondary battery and reduces electrode polarization. Simultaneously, controlling the d1 range allows for precise control of the size of the first particle, optimizing its size matching with the second particle, enhancing the filling effect between the second particles, and increasing the compaction density of the cathode material, thereby optimizing the energy density of the secondary battery. It should be noted that the average diameter of the first lithium iron phosphate matrix can be calculated by subtracting twice the thickness of the first carbon coating layer from the particle size of the first particle after measuring the particle size and the thickness of the first carbon coating layer.
[0065] It should be noted that by adjusting the sintering temperature and sintering time of the first high-temperature sintering treatment, the grain growth rate of the first lithium iron phosphate matrix can be controlled, thereby adjusting the size of d1. The higher the sintering temperature and the longer the sintering time, the larger d1 is; conversely, the lower the sintering temperature and the shorter the sintering time, the smaller d1 is.
[0066] In one specific embodiment, the average diameter of the second lithium iron phosphate matrix is d2, and the value of d2 ranges from 0.984 to 3.998 μm.
[0067] By precisely controlling the value of d2 within the range of 0.984~3.998μm, the solid-phase transport path of lithium ions within the second particle can be effectively adjusted, improving the matching degree of lithium ion insertion / extraction rates between the second and first particles, optimizing the kinetic performance of the cathode material, and thus improving the rate performance of the secondary battery and reducing electrode polarization. Simultaneously, adjusting the d2 range allows for precise control of the size of the second particle, optimizing both the inter-particle size and the structural stability of the second particle itself. This provides a stable framework support system for the filling of the first particle, thereby increasing the compaction density of the cathode material and improving the energy density of the secondary battery. It should be noted that the average diameter of the second lithium iron phosphate matrix can be calculated by subtracting twice the thickness of the second carbon coating layer from the particle size of the second particle after measuring the particle size and the thickness of the second carbon coating layer.
[0068] It should be noted that by adjusting the sintering temperature and sintering time of the second high-temperature sintering treatment, the grain growth rate of the second lithium iron phosphate matrix can be controlled, thereby adjusting the size of d2. The higher the sintering temperature and the longer the sintering time, the larger d2 is; conversely, the smaller d2 is.
[0069] In one specific implementation, a = d2 - d1, b = h1 - h2;
[0070] n = a × b, where the value of n ranges from 0.0019 to 0.055.
[0071] It should be noted that 'a' represents the difference in average diameter between the first and second lithium iron phosphate substrates. This parameter directly affects the filling matching degree between the first and second particles, thereby controlling the compaction density of lithium iron phosphate. 'b' represents the difference in thickness between the first and second carbon coating layers. This parameter can control the size of the first and second particles, further adjusting the matching relationship between the particles. Simultaneously, it can also control the improvement effect on the kinetic performance degradation caused by the uneven lithium insertion / extraction due to differences in the lithium extraction paths of the first and second lithium iron phosphate substrates, thus achieving the adjustment of the kinetic performance of lithium iron phosphate.
[0072] Specifically, by establishing the relationship n=a×b and limiting the value of n to a range of 0.0019~0.055, the particle size difference 'a' and the carbon coating thickness difference 'b' are dynamically balanced. This range ensures the close-packing effect of the first and second particles, improves the compaction density of lithium iron phosphate, and compensates for the differences in lithium-ion transport paths caused by particle size differences, thus mitigating the polarization effect caused by uneven lithium insertion / extraction. This design can achieve synergistic optimization of matrix particle size differences and carbon coating thickness differences. It can ensure the matching degree of particle gradation and maintain the close-packed structure to achieve high compaction density, while effectively compensating for the deviation in lithium insertion / extraction rate caused by the average diameter difference of the lithium iron phosphate matrix, mitigating the polarization accumulation and kinetic degradation problems caused by uneven lithium insertion / extraction. This allows the particle filling structure and electrochemical kinetic characteristics to form a dynamic balance, ultimately achieving synchronous optimization of the cathode material's compaction density and kinetic performance, and synergistically improving the energy density and rate performance of the secondary battery.
[0073] To further optimize the compaction density and kinetic performance of the cathode material, in one specific embodiment, the value of n ranges from 0.0024 to 0.0243. Within this range, the energy density and rate performance of the secondary battery reach a better level.
[0074] In one specific implementation, the value of a ranges from 0.9 to 3.8 μm.
[0075] By precisely controlling α to be 0.9~3.8μm, the size difference between the first and second lithium iron phosphate substrates can be effectively adjusted, thereby regulating the size of the first and second particles, optimizing the particle matching relationship between them, and thus improving the compaction density of the cathode material, achieving further optimization of the energy density of the secondary battery. In a preferred embodiment, α is 1~3μm.
[0076] It should be noted that the grain growth rate of the first and second lithium iron phosphate substrates can be controlled by adjusting the sintering temperature and time of the first and second particles, thereby adjusting the value of 'a'. The higher the sintering temperature and the longer the sintering time of the first lithium iron phosphate substrate, and the lower the sintering temperature and the shorter the sintering time of the second lithium iron phosphate substrate, the smaller 'a' will be, and vice versa. The particle size can also be controlled by adjusting the number of milling cycles of the first and second particles. More milling cycles result in smaller particle sizes and smaller lithium iron phosphate grain sizes, thus controlling the value of 'a'. More milling cycles for the first particle and fewer milling cycles for the second particle result in a smaller 'a', and vice versa.
[0077] In one specific implementation, the value of b ranges from 0.001 to 0.015 μm.
[0078] By precisely controlling b to be 0.001~0.015μm, the thickness difference between the first and second carbon coating layers can be effectively adjusted, thereby regulating the difference in lithium-ion insertion / extraction paths between them, reducing the difference in lithium insertion / extraction rates between the first and second particles, and thus improving the kinetic performance of the cathode material, thereby enhancing the rate performance of the secondary battery. In a preferred embodiment, b is 0.002~0.009μm.
[0079] In one specific embodiment, the mass ratio of the first particle to the second particle is (0.5~4.99):(5~9.99).
[0080] By precisely controlling the mass ratio of the first particle to the second particle in the lithium iron phosphate material to (0.5~4.99):(5~9.99), the relative content of the two particles in the material can be effectively adjusted, further optimizing the dense packing effect between particles, improving the compaction density of the lithium iron phosphate material, and thus improving the energy density of the secondary battery.
[0081] In one specific embodiment, the lithium iron phosphate further includes a third particle, which includes a third lithium iron phosphate matrix and a third carbon coating layer disposed on at least a portion of the surface of the third lithium iron phosphate matrix.
[0082] The particle size of the third particle is D3, and the value of D3 ranges from 0.12 to 0.8 μm;
[0083] The thickness of the third carbon coating layer is h3,1
[0084] By introducing a third particle with a particle size between the first and second particles, a three-level filling system is constructed, and the particle size D3 of the third particle is controlled to be 0.12~0.8μm. This allows the third particle to form a transition layer between the nanoscale first particle and the micrometer-scale second particle, further improving the compaction density of the cathode material; simultaneously, it enables 1
[0085] The present invention does not specifically limit the preparation method of the third particle, but by way of example, it may include the following steps:
[0086] 1) The third phosphate, lithium source, carbon source, dopant and solvent are mixed and dispersed to obtain the third particle mixed slurry;
[0087] 2) The third particle mixed slurry is subjected to sand milling to obtain the third particle slurry (D50 particle size is 200~400nm).
[0088] 3) The third particle slurry is spray-dried to obtain the third particle raw material (D50 particle size is 20~60μm);
[0089] 4) The third raw material is subjected to a second high-temperature sintering treatment to obtain the third sintered material;
[0090] 5) The third sintered material is crushed and deagglomerated to obtain the third particle.
[0091] The prepared third particle is mixed with the first and second particles to obtain lithium iron phosphate material.
[0092] It should be noted that in the third particle mixed slurry, the mass ratio of the third iron phosphate, lithium source, carbon source, dopant and solvent is 1000:(249~254):(5~20):(4~22):(2300~2400).
[0093] It should be noted that the Fe / P ratio of the third ferric phosphate is 0.95~1.
[0094] It should be noted that h3 can be controlled by adjusting the temperature of the second high-temperature sintering process during preparation. The higher the sintering temperature, the more thorough the carbonization, and thus the smaller h3. In a preferred embodiment, the second high-temperature sintering temperature of the third particle is 680~850℃. h3 can also be controlled by adjusting the amount of carbon source used; the higher the amount of carbon source, the larger h3. In a preferred embodiment, the mass percentage of the carbon source ranges from 5% to 15%.
[0095] To further optimize the kinetic performance of the cathode material, in one specific implementation, the value of h1 / h3 ranges from 0.005 to 2.5.
[0096] By precisely controlling h1 / h3 to 0.005~2.5, the compaction density and kinetic properties of the cathode material are further improved, resulting in better energy density and rate performance of the secondary battery.
[0097] In one specific implementation, the value of h3 ranges from 0.002 to 0.02 μm.
[0098] By precisely controlling the thickness h3 of the third carbon coating layer to be 0.002~0.02μm, the lithium-ion insertion / extraction behavior of the third particle can be effectively controlled, reducing the ion transport difference between the third particle and the first and second particles, and further optimizing the kinetic performance of lithium iron phosphate. Simultaneously, this thickness range can optimize the filling matching relationship between the third particle and the first and second particles, further improving the compaction density of lithium iron phosphate. In a preferred embodiment, h3 is 0.005~0.007μm.
[0099] In one specific embodiment, the mass ratio of the first particle, the second particle, and the third particle is (0.001~0.2):(0.5~0.999):(0.2~0.3).
[0100] By precisely controlling the mass ratio of the first, second, and third particles to (0.001~0.2):(0.5~0.999):(0.2~0.3), the relative content of the three particles can be adjusted, giving full play to the overfilling effect of the third particle on the first and second particles, further improving the compaction density of lithium iron phosphate material, and achieving a better level of energy density for secondary batteries.
[0101] In one specific implementation, h2 <h3
[0102] By constructing a distribution relationship where the thickness of the carbon coating layer decreases stepwise (h2) <h3
[0103] In one specific embodiment, the lithium iron phosphate further includes a fourth particle, which includes a fourth lithium iron phosphate matrix and a fourth carbon coating layer disposed on at least a portion of the surface of the fourth lithium iron phosphate matrix.
[0104] The particle size of the fourth particle is D4, and the value of D4 ranges from 4 to 35 μm;
[0105] The thickness of the fourth carbon coating layer is h4,1
[0106] By introducing a fourth particle with a diameter of 4-35 μm, a four-level close-packed system is formed together with the first, second, and third particles as the framework structure of lithium iron phosphate, further improving the compaction density of the cathode material. Simultaneously, the thickness h4 of the fourth carbon coating layer satisfies 1...
[0107] The present invention does not specifically limit the preparation method of the fourth particle, but by way of example, it may include the following steps:
[0108] 1) The fourth phosphate, lithium source, carbon source, dopant and solvent are mixed and dispersed to obtain the fourth particle mixed slurry;
[0109] 2) The fourth particle mixed slurry is subjected to sand milling to obtain the fourth particle slurry (D50 particle size is 100~400nm).
[0110] 3) The fourth particle slurry is subjected to fluid drying treatment to obtain the fourth particle raw material (D50 particle size is 4~40μm);
[0111] 4) The fourth raw material is subjected to a second high-temperature sintering treatment to obtain the fourth sintered material;
[0112] 5) The fourth sintered material is subjected to vibration sieving to obtain the fourth particle.
[0113] The prepared fourth particle was mixed with the first, second, and third particles to obtain lithium iron phosphate material.
[0114] It should be noted that in the fourth particle mixed slurry, the mass ratio of the fourth iron phosphate, lithium source, carbon source, dopant and solvent is 1000:(249~254):(5~20):(4~22):(2300~2400).
[0115] It should be noted that the Fe / P ratio of ferric phosphate is 0.96~1.
[0116] It should be noted that the fluid drying process can be carried out using at least one of two-fluid or multi-fluid media, with an inlet air temperature of 180~220℃ and a feed rate of 25~70m. 3 / h, with an outlet air temperature of 80~100℃.
[0117] It should be noted that the mesh size of the vibrating screen used for vibrating sieving is 50~500 mesh.
[0118] It should be noted that h4 can be adjusted by regulating the temperature of the second high-temperature sintering process; the higher the sintering temperature, the smaller h4. h4 can also be adjusted by regulating the sintering time of the second high-temperature sintering process; the longer the sintering time, the smaller h4.
[0119] In one specific implementation, the value of h4 ranges from 0.001 to 0.015 μm.
[0120] By precisely controlling h4 to be 0.001~0.015μm, the lithium-ion insertion / extraction behavior of the fourth particle is optimized while maintaining the continuity of the conductive network. This reduces the ion transport differences between the fourth particle and the first, second, and third particles, further optimizing the kinetic performance of lithium iron phosphate. Simultaneously, this thickness range optimizes the filling matching relationship between the fourth particle and other particles, further optimizing the compaction density of the cathode material.
[0121] In one specific embodiment, the mass ratio of the first particle, the second particle, the third particle, and the fourth particle is (0.001~0.1):(0.5~0.9):(0.25~0.499):(0.001~0.15).
[0122] By precisely controlling the mass ratio of the first, second, third, and fourth particles to (0.001~0.1):(0.5~0.9):(0.25~0.499):(0.001~0.15), the relative content ratio of the four-level particles within the lithium iron phosphate material can be adjusted, achieving efficient close-packing and synergistic matching among the four-level particles. This further improves the compaction density of the lithium iron phosphate material, thereby enabling the secondary battery to achieve a better energy density.
[0123] In one specific embodiment, the powder conductivity of the positive electrode material is 2~500 Ω·cm.
[0124] Specifically, by precisely controlling the resistivity of the cathode material powder to be 2~500 Ω·cm, its electron transport capability can be effectively improved, and the ion migration rate can be controlled, thereby optimizing the kinetic performance and improving the rate performance of the secondary battery. In a preferred embodiment, the resistivity of the cathode material powder is 10~50 Ω·cm.
[0125] Secondly, the present invention proposes a positive electrode sheet, which includes the aforementioned positive electrode material; the porosity of the positive electrode sheet is 10% to 40%. Thanks to the filling structure within the positive electrode material, the positive electrode sheet naturally possesses excellent compaction density and kinetic properties.
[0126] Furthermore, by precisely controlling the porosity of the positive electrode sheet to be between 10% and 40%, while ensuring compaction density, the electrolyte can more uniformly and fully wet the positive electrode material and achieve sufficient contact with lithium iron phosphate, optimizing the lithium-ion transport path, reducing migration resistance, and improving the rate performance of the secondary battery. Simultaneously, within this porosity range, the positive electrode sheet can maintain better structural integrity and mechanical stability, effectively extending the cycle life of the secondary battery.
[0127] It should be noted that the porosity of the positive electrode sheet can be tested using the following method: The pre-treated positive electrode sheet is cut into circular sheets with a radius r of 6 mm using an electrode sheet punching machine. Simultaneously, the thickness of the positive electrode sheet and the current collector is measured using a thickness gauge, denoted as H1 and H2 respectively. The mass is then weighed using a balance with an accuracy of 0.00001 g and recorded as m1. According to the formula V=πr... 2 Calculate the volume V of the cut positive electrode sheet (H1-H2); completely immerse the positive electrode sheet in a sealed container of hexadecane for 1 hour; after immersion, remove the positive electrode sheet and blot it dry on filter paper until constant weight, then weigh it using a balance and record the mass as m2. Calculate its porosity using the following formula: Porosity = (m2-m1) / (ρV), where ρ is the density of hexadecane, 0.7734 g / cm³. 3 Porosity is expressed in percent.
[0128] It should be noted that the present invention does not specifically limit the preparation method of the positive electrode sheet. Exemplarily, it may include the following steps: mixing the positive electrode active material, conductive agent, and binder, adding N-methylpyrrolidone (NMP) solvent, and stirring under vacuum until the system is homogeneous to obtain a positive electrode slurry; uniformly coating the positive electrode slurry onto one surface of the positive electrode current collector, then coating it onto the other side, air-drying at room temperature, transferring it to an oven for further drying, and then cold-pressing and slitting to obtain the positive electrode sheet. The mass ratio of the positive electrode active material, conductive agent, and binder is 95~98wt%:0~1wt%:0.5~3wt%.
[0129] Thirdly, this invention proposes a secondary battery, which includes the aforementioned positive electrode sheet. Benefiting from the excellent compaction density and kinetic performance of this positive electrode sheet, this secondary battery possesses both excellent energy density and rate performance, and can be widely used in fields with stringent requirements for battery volumetric energy density and fast charging speed, such as new energy passenger vehicles, portable electronic devices, power tools, rail transportation, and energy storage power stations, thus having broad market application prospects.
[0130] In one specific embodiment, the secondary battery further includes a negative electrode sheet, which comprises a negative electrode material with an average particle size of 5~20μm.
[0131] By precisely controlling the average particle size of the negative electrode material to 5~20μm, it matches the multi-level particle structure of the positive electrode material, optimizes the synergistic transport of lithium ions between the positive and negative electrodes, reduces interfacial polarization, and improves the rate performance of the secondary battery.
[0132] The present invention does not specifically limit the preparation method of the negative electrode sheet. Exemplarily, it may include the following steps: mixing negative electrode active material, conductive agent, binder and dispersant, adding solvent to obtain negative electrode slurry, wherein the mass ratio of negative electrode active material: conductive agent: binder: dispersant is (90~98):(0~0.5):(1.5~5):(0.3~1.5), coating the negative electrode slurry on at least one surface of the negative electrode current collector, drying, rolling and cutting to obtain the negative electrode sheet.
[0133] In one specific embodiment, the negative electrode material includes graphite material, which includes primary particles and secondary particles;
[0134] The ratio of primary particles to secondary particles is 0.01 to 5.
[0135] Specifically, when graphite is used as the negative electrode active material, its unique layered structure allows for reversible lithium-ion insertion and extraction. This process exhibits excellent thermodynamic stability, and the material shows minimal volume deformation during charge and discharge, significantly optimizing the structural stability of the negative electrode and improving the cycle life of the secondary battery. Furthermore, precisely controlling the average particle size of graphite to 5-20 nm effectively leverages its excellent electronic conductivity, reducing the interfacial impedance of the negative electrode, optimizing its kinetic performance, and further enhancing the rate performance of the secondary battery. In addition, graphite offers advantages such as abundant raw material reserves, mature manufacturing processes, and low cost, making it suitable for large-scale industrial applications.
[0136] Furthermore, the graphite material comprises primary and secondary particles. By controlling the ratio of primary to secondary particles to 0.01–5, a two-dimensional close-packed negative electrode active material system can be constructed, significantly improving the compaction density of the negative electrode and thus optimizing its energy density. Simultaneously, the graphite material matched with the secondary particles can form a more continuous three-dimensional conductive network, effectively reducing the electron transport impedance of the negative electrode and further optimizing its kinetic performance. It should be noted that primary graphite particles refer to independent graphite crystal units, while secondary particles are aggregates formed by granulation and graphitization of multiple primary particles.
[0137] The negative electrode, in synergy with the aforementioned positive electrode, can produce a secondary battery with superior overall performance, achieving better rate performance, energy density, and cycle stability.
[0138] It is understood that, in addition to graphite, the negative electrode material also includes binders and conductive agents. This invention does not limit the specific type of binder for the negative electrode material, and includes, but is not limited to, at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate. This invention does not limit the specific type of conductive agent for the negative electrode material, and includes, but is not limited to, at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.
[0139] In addition to the negative electrode material, the negative electrode sheet also includes a negative electrode current collector. This invention does not limit the specific type of the negative electrode current collector, but includes, but is not limited to, at least one of copper foil, nickel foam, and copper foam.
[0140] It is understood that the secondary battery also includes a separator. This invention does not limit the specific type of separator, but includes, but is not limited to, one of the following: polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven fabric separator, and separator with ceramic coating.
[0141] In one specific embodiment, the secondary battery further includes an electrolyte with an ionic conductivity of 2~30 mS / cm.
[0142] By precisely controlling the ionic conductivity of the electrolyte to 2~30 mS / cm, the migration rate of lithium ions in the electrolyte can be optimized, matching its transport path with that of lithium ions at the positive and negative electrode interfaces. This effectively reduces concentration polarization within the battery, optimizes the insertion / extraction rate of lithium ions at the positive and negative electrode interfaces, and improves the kinetic performance of the secondary battery. Simultaneously, it can achieve synergistic adaptation with multi-level particle structure positive and negative electrodes, fully leveraging the advantages of the electrode structure to achieve a synergistic improvement in energy density and kinetic performance of the secondary battery. This significantly enhances the overall kinetic performance, cycle stability, and lifespan of the secondary battery, ultimately achieving global synergistic matching of all components in a high-performance secondary battery.
[0143] In one specific embodiment, the electrolyte includes a solvent, which includes a carboxylic acid ester; the carboxylic acid ester has a mass percentage content of 5 wt% to 30 wt% based on the mass of the solvent.
[0144] Specifically, when the solvent includes carboxylic acid esters, such solvents can effectively reduce the viscosity of the electrolyte, improve the wetting effect of the electrolyte on the positive and negative electrodes, and effectively control the ionic conductivity of the electrolyte from 2 to 30 mS / cm, optimizing the migration path and rate of lithium ions and significantly improving the rate performance of the secondary battery. Furthermore, these solvents can participate in the formation of the SEI film, effectively suppressing the degree of side reactions between the electrolyte and the active material, reducing irreversible lithium ion consumption, and significantly improving the cycle stability and capacity retention of the secondary battery. It should be noted that the viscosity of the electrolyte can be measured using a digital viscometer at 25°C.
[0145] When the mass percentage of carboxylic acid ester is 5wt%~30wt%, it can significantly improve the matching degree between the lithium ion migration rate of the electrolyte and the insertion / extraction rate of the electrode, and participate in the formation of an SEI film with lower impedance and higher stability, thereby greatly improving the rate performance, cycle stability and capacity retention of the secondary battery.
[0146] The present invention does not limit the specific type of carboxylic acid ester, including but not limited to at least one of methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), methyl propionate (MP), ethyl propionate (EP), methyl butyrate (MB), and ethyl butyrate (EB).
[0147] It is understood that, in addition to the solvent, the electrolyte also includes lithium salts. This invention does not limit the specific type of lithium salt, but includes, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0148] In one specific embodiment, the solvent further includes carbonate, wherein a single molecule of carbonate contains 3 to 6 carbon atoms.
[0149] Specifically, when the solvent includes carbonates, their outstanding resistance to oxidation and reduction, along with high thermal stability and safety, can significantly improve the stability of the electrolyte during cycling, thereby enhancing the overall cycle safety of the secondary battery. Furthermore, selecting carbonates with 3-6 carbon atoms per molecule can effectively control the electrolyte's ionic conductivity to 2-30 mS / cm, further improving the compatibility between the solvent and the secondary battery, and optimizing the overall performance of the secondary battery.
[0150] It should be noted that the mass percentage of carbonate is 75wt%~85wt% based on the mass of the solvent.
[0151] It should be noted that the present invention does not limit the specific type of carbonate, including but not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC).
[0152] Fourthly, this invention proposes an electrical device comprising the aforementioned secondary battery. Benefiting from the excellent rate capability, energy density, and cycle life of this secondary battery, the electrical device can achieve efficient and sustained operation by relying on its stable energy supply and efficient charge / discharge characteristics, effectively improving the device's battery life and user experience, and possessing broad application scenarios. The electrical device of this invention may include, but is not limited to, electric vehicles (such as pure electric vehicles, hybrid electric vehicles, and electric bicycles), consumer electronic devices (such as smartphones, laptops, and wearable devices), energy storage devices (such as home energy storage cabinets, industrial energy storage systems, and photovoltaic energy storage power stations), and power tools (such as electric drills, electric wrenches, and electric saws).
[0153] The cathode material of this application will be further described in detail below through specific embodiments.
[0154] Example 1
[0155] The secondary battery in this embodiment is prepared through the following steps:
[0156] 1) Lithium hydroxide monohydrate, ferrous sulfate heptahydrate, phosphoric acid (concentration 85%), and ultrapure water were mixed in a mass ratio of 0.167:1:0.433:3.56 to obtain a first particle slurry. The first particle slurry was subjected to a hydrothermal reaction in a hydrothermal reactor at 170℃ for 8 hours to obtain lithium iron phosphate powder. The lithium iron phosphate powder was then mixed with sucrose, polyethylene glycol (PEG) (Mn:6000), vanadium pentoxide dopant, and pure water in a mass ratio of 100:6:4:0.7:246 and ground to obtain a first particle slurry (D50 particle size 200nm). The grinding process was repeated 16 times at a milling speed of 600rpm. The first particle slurry was then spray-dried at an inlet air temperature of 200℃ and a feed rate of 30m³ / h. 3 / h; outlet air temperature 90℃, to obtain the first raw material particles; the first raw material particles are subjected to the first high-temperature sintering treatment in a nitrogen atmosphere at a temperature of 690℃ for 11h to obtain the first sintered material particles; subsequently, the first sintered material particles are subjected to airflow pulverization treatment at a pulverization pressure of 400mPa and a grading frequency of 70Hz to obtain the first particles.
[0157] 2) The second-particle iron phosphate (Fe / P = 0.96), lithium carbonate, sucrose, PEG (Mn: 6000), dopant titanium dioxide, and ultrapure water were mixed and dispersed in a mass ratio of 1000:251.5:6:4:15:2300 to obtain a second-particle mixed slurry. The second-particle mixed slurry was milled 16 times to obtain a second-particle slurry (D50 particle size of 450 nm). The second-particle slurry was spray-dried to obtain a second-particle raw material (D50 particle size of 27 μm). The second-particle raw material was subjected to a second high-temperature sintering treatment under a nitrogen atmosphere at a temperature of 740 °C for 9 h to obtain a second-particle sintered material. The second-particle sintered material was then pulverized and deagglomerated to obtain the second particles.
[0158] 3) The first and second particles obtained are mechanically mixed at a mass ratio of 0.1:0.6 to obtain lithium iron phosphate material. The lithium iron phosphate material, conductive agent (SP), and binder (PVDF) are mixed at a mass ratio of 97:0.5:2.5 to obtain cathode material 1.
[0159] 4) Add the positive electrode material to the solvent NMP and stir under vacuum until the system is homogeneous to obtain the positive electrode slurry; coat the positive electrode slurry evenly on one surface of the positive electrode current collector aluminum foil, and then coat it on the other side in sequence. After drying at room temperature, transfer it to an oven for further drying, and then obtain the positive electrode sheet by cold pressing and slitting.
[0160] 5) Mix graphite material, conductive agent SP, PVDF and CMC in a mass ratio of 97:0.2:1.8:1, add NMP to obtain negative electrode slurry, coat the negative electrode slurry on at least one surface of the negative electrode current collector, dry, roll and cut to obtain negative electrode sheet.
[0161] 6) Mix EC, EMC, DEC, and FEC in a volume ratio of 30:50:15:5 to obtain an organic solvent. Then, dissolve fully dried lithium salts LiPF6 and LiFSI in the mixed organic solvent at a mass ratio of 9:1 to prepare an electrolyte with a lithium salt concentration of 1 mol / L. The ionic conductivity of the electrolyte is 8 mS / cm.
[0162] 7) Stack the above positive electrode sheet, separator PP and negative electrode sheet in sequence, so that the separator is between the positive and negative electrode sheets to play the role of isolation, and then wind them to obtain the bare cell; place the bare cell in the outer packaging shell, dry it and inject electrolyte, and after vacuum sealing, standing, formation and shaping processes, obtain the secondary battery 1.
[0163] Example 2
[0164] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 12, the grading frequency is adjusted to 70Hz, the first high-temperature sintering temperature is adjusted to 670℃, and the sintering time is adjusted to 13h. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 720℃, and the number of milling cycles in the second milling treatment is adjusted to 14. This embodiment yields secondary battery 2.
[0165] Example 3
[0166] This embodiment is basically the same as Embodiment 1, except that the number of milling operations in step 1 is adjusted to 10, the grading frequency is adjusted to 80Hz, the first high-temperature sintering temperature is adjusted to 700℃, and the sintering time is adjusted to 7 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 720℃, the sintering time is adjusted to 14 hours, the number of milling operations in the second milling treatment is adjusted to 16, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:10. This embodiment yields secondary battery 3.
[0167] Example 4
[0168] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 17, the grading frequency is adjusted to 60Hz, the first high-temperature sintering temperature is adjusted to 650℃, and the sintering time is adjusted to 12 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 730℃, the sintering time is adjusted to 19 hours, and the number of milling cycles in the second milling treatment is adjusted to 15. This embodiment yields secondary battery 4.
[0169] Example 5
[0170] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 18, the grading frequency is adjusted to 60Hz, the first high-temperature sintering temperature is adjusted to 680℃, and the sintering time is adjusted to 12 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 750℃, the sintering time is adjusted to 4 hours, the number of milling cycles in the second milling treatment is adjusted to 17, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:8. This embodiment yields secondary battery 5.
[0171] Example 6
[0172] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 12, the grading frequency is adjusted to 50Hz, the first high-temperature sintering temperature is adjusted to 730℃, and the sintering time is adjusted to 6 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 680℃, the sintering time is adjusted to 9 hours, and the number of milling cycles in the second milling treatment is adjusted to 10. This embodiment yields secondary battery 6.
[0173] Example 7
[0174] This embodiment is basically the same as Embodiment 1, except that the number of milling operations in step 1 is adjusted to 11, the grading frequency is adjusted to 50Hz, the first high-temperature sintering temperature is adjusted to 690℃, and the sintering time is adjusted to 10 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 710℃, the sintering time is adjusted to 4 hours, the number of milling operations in the second milling treatment is adjusted to 11, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:4. This embodiment yields secondary battery 7.
[0175] Example 8
[0176] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 18, the grading frequency is adjusted to 70Hz, the first high-temperature sintering temperature is adjusted to 680℃, and the sintering time is adjusted to 6 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 760℃, the sintering time is adjusted to 4 hours, the number of milling cycles in the second milling treatment is adjusted to 16, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:4. This embodiment yields a secondary battery 8.
[0177] Example 9
[0178] This embodiment is basically the same as Embodiment 1, except that the number of milling operations in step 1 is adjusted to 2, the grading frequency is adjusted to 60Hz, the first high-temperature sintering temperature is adjusted to 690℃, and the sintering time is adjusted to 9 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 700℃, the sintering time is adjusted to 19 hours, and the number of milling operations in the second milling treatment is adjusted to 11. This embodiment yields a secondary battery 9.
[0179] Example 10
[0180] This embodiment is basically the same as Embodiment 1, except that the number of milling operations in step 1 is adjusted to 11, the grading frequency is adjusted to 80Hz, the first high-temperature sintering temperature is adjusted to 710℃, and the sintering time is adjusted to 12 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 720℃, the sintering time is adjusted to 14 hours, the number of milling operations in the second milling treatment is adjusted to 15, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:8. This embodiment yields a secondary battery 10.
[0181] Example 11
[0182] This embodiment is basically the same as Embodiment 1, except that the number of milling operations in step 1 is adjusted to 12, the grading frequency is adjusted to 80Hz, the first high-temperature sintering temperature is adjusted to 730℃, and the sintering time is adjusted to 6 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 730℃, the sintering time is adjusted to 14 hours, the number of milling operations in the second milling treatment is adjusted to 17, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:10. This embodiment yields a secondary battery 11.
[0183] Example 12
[0184] This embodiment is basically the same as Embodiment 1, except that the number of milling operations in step 1 is adjusted to 14, the grading frequency is adjusted to 80Hz, the first high-temperature sintering temperature is adjusted to 700℃, and the sintering time is adjusted to 6 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 750℃, the sintering time is adjusted to 19 hours, the number of milling operations in the second milling treatment is adjusted to 16, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:5. This embodiment yields a secondary battery 12.
[0185] Example 13
[0186] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 20, the grading frequency is adjusted to 70Hz, the first high-temperature sintering temperature is adjusted to 720℃, and the sintering time is adjusted to 6 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 760℃, the sintering time is adjusted to 4 hours, the number of milling cycles in the second milling treatment is adjusted to 18, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:8. This embodiment yields a secondary battery 13.
[0187] Example 14
[0188] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 7, the grading frequency is adjusted to 50Hz, the first high-temperature sintering temperature is adjusted to 710℃, and the sintering time is adjusted to 6 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 710℃, the sintering time is adjusted to 9 hours, and the number of milling cycles in the second milling treatment is adjusted to 12. This embodiment yields a secondary battery 14.
[0189] Example 15
[0190] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 12, the grading frequency is adjusted to 50Hz, the first high-temperature sintering temperature is adjusted to 710℃, and the sintering time is adjusted to 7 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 750℃, the sintering time is adjusted to 12.5 hours, and the number of milling cycles in the second milling treatment is adjusted to 17. This embodiment yields a secondary battery 15.
[0191] Example 16
[0192] This embodiment is basically the same as Embodiment 1, except that the number of milling cycles in step 1 is adjusted to 12, the grading frequency is adjusted to 40Hz, the first high-temperature sintering temperature is adjusted to 650℃, and the sintering time is adjusted to 11 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 750℃, the sintering time is adjusted to 14 hours, and the number of milling cycles in the second milling treatment is adjusted to 17. This embodiment yields a secondary battery 16.
[0193] Example 17
[0194] This embodiment is basically the same as Embodiment 1, except that the number of milling operations in step 1 is adjusted to 8, the grading frequency is 50Hz, the first high-temperature sintering temperature is 680℃, and the sintering time is adjusted to 9 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 755℃, the sintering time is adjusted to 12.5 hours, the number of milling operations in the second milling treatment is 18, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:7. This embodiment yields a secondary battery 17.
[0195] Example 18
[0196] The secondary battery in this embodiment is prepared through the following steps:
[0197] 1) Lithium hydroxide monohydrate, ferrous sulfate heptahydrate, phosphoric acid (concentration 85%), and ultrapure water were mixed in a mass ratio of 0.167:1:0.433:3.56 to obtain a first particle slurry. The first particle slurry was subjected to a hydrothermal reaction in a hydrothermal reactor at 170℃ for 8 hours to obtain lithium iron phosphate powder. The lithium iron phosphate powder was then mixed with sucrose, PEG (Mn:6000), vanadium pentoxide dopant, and pure water in a mass ratio of 100:6:4:0.7:246 and ground to obtain a first particle slurry (D50 particle size 200nm). The grinding process was repeated 17 times at a milling speed of 600rpm. The first particle slurry was then spray-dried at an inlet air temperature of 200℃ and a feed rate of 30m³ / h. 3 / h; outlet air temperature 90℃, to obtain the first raw material particles; the first raw material particles are subjected to the first high-temperature sintering treatment in a nitrogen atmosphere at a temperature of 690℃ for 8 hours to obtain the first sintered material particles; subsequently, the first sintered material particles are subjected to airflow pulverization treatment at a pulverization pressure of 400mPa and a grading frequency of 40Hz to obtain the first particles.
[0198] 2) The second-particle iron phosphate (Fe / P = 0.96), lithium carbonate, sucrose, PEG (Mn: 6000), dopant titanium dioxide, and ultrapure water were mixed and dispersed in a mass ratio of 1000:251.5:4:4:15:2300 to obtain a second-particle mixed slurry. The second-particle mixed slurry was milled 16 times at a speed of 600 rpm to obtain a second-particle slurry (D50 particle size of 450 nm). The second-particle slurry was spray-dried to obtain a second-particle raw material (D50 particle size of 27 μm). The second-particle raw material was subjected to a second high-temperature sintering treatment under a nitrogen atmosphere at a temperature of 750 °C for 12.5 h to obtain a second-particle sintered material. The second-particle sintered material was then pulverized and deagglomerated to obtain the second particles.
[0199] 3) The third-particle iron phosphate (Fe / P = 0.98), lithium carbonate, sucrose, PEG (Mn: 6000), dopant titanium dioxide, and ultrapure water were mixed and dispersed in a mass ratio of 1000:253:4:4:18:2300 to obtain a third-particle mixed slurry. The third-particle mixed slurry was milled 10 times at a speed of 600 rpm to obtain a third-particle slurry (D50 particle size of 350 nm). The third-particle slurry was spray-dried to obtain a third-particle raw material (D50 particle size of 25 μm). The third-particle raw material was sintered at high temperature under a nitrogen atmosphere at 750 °C for 12 h to obtain a third-particle sintered material. The third-particle sintered material was then pulverized and deagglomerated at a pulverization pressure of 450 mPa and a classification frequency of 55 Hz to obtain the third particles (h3 = 0.01 μm, D3 = 0.6 μm, d3 = 0.58 μm).
[0200] 4) The first, second, and third particles obtained in steps 1-3 are mechanically mixed in a mass ratio of 0.1:0.6:0.2 to obtain lithium iron phosphate material. The lithium iron phosphate material, conductive agent (SP), and binder (PVDF) are mixed in a mass ratio of 97:0.5:2.5 to obtain the cathode material.
[0201] Steps 5-8 are basically the same as steps 4-7 in Example 1. In this example, a secondary battery 18 is obtained.
[0202] Example 19
[0203] The secondary battery in this embodiment is prepared through the following steps:
[0204] 1) Lithium hydroxide monohydrate, ferrous sulfate heptahydrate, phosphoric acid (concentration 85%), and ultrapure water were mixed in a mass ratio of 0.167:1:0.433:3.56 to obtain the first particle slurry. The first particle slurry was subjected to a hydrothermal reaction in a hydrothermal reactor at a reaction temperature of 170℃ for 8 hours to obtain lithium iron phosphate powder. The lithium iron phosphate powder was mixed with sucrose, PEG (Mn:6000), vanadium pentoxide dopant, and pure water in a mass ratio of 100:6:4:0.7:246 and ground to obtain the first particle slurry (D50 particle size of 200nm). The grinding process was repeated 12 times at a milling speed of 600rpm. The first particle slurry was then spray-dried at an inlet air temperature of 200℃ and a feed rate of 30m. 3 / h; outlet air temperature 90℃, to obtain the first raw material particles; the first raw material particles are subjected to the first high-temperature sintering treatment in a nitrogen atmosphere at a temperature of 650℃ for 11h to obtain the first sintered material particles; subsequently, the first sintered material particles are subjected to airflow pulverization treatment at a pulverization pressure of 400mPa and a grading frequency of 40Hz to obtain the first particles.
[0205] 2) The second-particle iron phosphate (Fe / P = 0.96), lithium carbonate, sucrose, PEG (Mn: 6000), dopant titanium dioxide, and ultrapure water were mixed and dispersed in a mass ratio of 1000:251.5:6:4:15:2300 to obtain a second-particle mixed slurry. The second-particle mixed slurry was milled 17 times at a speed of 600 rpm to obtain a second-particle slurry (D50 particle size of 450 nm). The second-particle slurry was spray-dried to obtain a second-particle raw material (D50 particle size of 27 μm). The second-particle raw material was subjected to a second high-temperature sintering treatment under a nitrogen atmosphere at a temperature of 750 °C for 14 h to obtain a second-particle sintered material. The second-particle sintered material was then pulverized and deagglomerated to obtain the second particles.
[0206] 3) The fourth particle, iron phosphate (Fe / P = 0.98), lithium carbonate, sucrose, dopant titanium dioxide, and ultrapure water were mixed and dispersed in a mass ratio of 1000:252.5:10:20:2300 to obtain a fourth particle mixed slurry. The fourth particle mixed slurry was milled 7 times at a speed of 600 rpm to obtain a fourth particle slurry (D50 particle size = 250 nm). The fourth particle slurry was subjected to two-fluid spray drying to obtain a fourth particle raw material (D50 particle size = 8 nm). The fourth particle raw material was subjected to high-temperature sintering under a nitrogen atmosphere at a temperature of 780℃ for 8 hours to obtain a fourth particle sintered material. The fourth particle sintered material was subjected to vibratory sieving (through a 250-mesh sieve) to obtain the fourth particle (h4 = 0.006 μm, D4 = 5 μm, d4 = 4.988 μm).
[0207] 4) The first, second, and third particles obtained in steps 1-3 are mechanically mixed in a mass ratio of 0.1:0.6:0.2 to obtain lithium iron phosphate material. The lithium iron phosphate material, conductive agent (SP), and binder (PVDF) are mixed in a mass ratio of 97:0.5:2.5 to obtain the cathode material.
[0208] Steps 5-8 are basically the same as steps 4-7 in Example 1. In this example, a secondary battery 19 is obtained.
[0209] Example 20
[0210] The secondary battery in this embodiment is prepared through the following steps:
[0211] 1) Lithium hydroxide monohydrate, ferrous sulfate heptahydrate, phosphoric acid (concentration 85%), and ultrapure water were mixed in a mass ratio of 0.167:1:0.433:3.56 to obtain a first particle slurry. The first particle slurry was subjected to a hydrothermal reaction in a hydrothermal reactor at 170℃ for 8 hours to obtain lithium iron phosphate powder. The lithium iron phosphate powder was then mixed with sucrose, PEG (Mn:6000), vanadium pentoxide dopant, and pure water in a mass ratio of 100:6:4:0.7:246 and ground to obtain a first particle slurry (D50 particle size 200nm). The grinding process was repeated 8 times at a milling speed of 600rpm. The first particle slurry was then spray-dried at an inlet air temperature of 200℃ and a feed rate of 30m³ / h. 3 / h; outlet air temperature 90℃, to obtain the first raw material particles; the first raw material particles are subjected to the first high-temperature sintering treatment in a nitrogen atmosphere at a temperature of 680℃ for 9 hours to obtain the first sintered material particles; subsequently, the first sintered material particles are subjected to airflow pulverization treatment at a pulverization pressure of 400mPa and a grading frequency of 50Hz to obtain the first particles.
[0212] 2) The second-particle iron phosphate (Fe / P = 0.96), lithium carbonate, sucrose, PEG (Mn: 6000), dopant titanium dioxide, and ultrapure water were mixed and dispersed in a mass ratio of 1000:251.5:7:4:15:2300 to obtain a second-particle mixed slurry. The second-particle mixed slurry was milled 18 times at a speed of 600 rpm to obtain a second-particle slurry (D50 particle size of 450 nm). The second-particle slurry was spray-dried to obtain a second-particle raw material (D50 particle size of 27 μm). The second-particle raw material was subjected to a second high-temperature sintering treatment under a nitrogen atmosphere at a temperature of 755 °C for 12.5 h to obtain a second-particle sintered material. The second-particle sintered material was then crushed and deagglomerated to obtain the second particles.
[0213] 3) The third-particle iron phosphate (Fe / P = 0.98), lithium carbonate, sucrose, PEG (Mn: 6000), dopant titanium dioxide, and ultrapure water were mixed and dispersed in a mass ratio of 1000:253:6:4:18:2300 to obtain a third-particle mixed slurry. The third-particle mixed slurry was milled 5 times to obtain a third-particle slurry (D50 particle size of 350 nm). The third-particle slurry was spray-dried to obtain a third-particle raw material (D50 particle size of 25 μm). The third-particle raw material was sintered at high temperature under a nitrogen atmosphere at 770 °C for 8 h to obtain a third-particle sintered material. The third-particle sintered material was then pulverized and deagglomerated under a pulverizing pressure of 450 mPa and a grading frequency of 55 Hz to obtain the third particles (h3 = 0.01 μm, D3 = 0.6 μm, d3 = 0.58 μm).
[0214] 4) The fourth particle, iron phosphate (Fe / P = 0.98), lithium carbonate, sucrose, dopant titanium dioxide, and ultrapure water were mixed and dispersed in a mass ratio of 1000:252.5:6:20:2300 to obtain a fourth particle mixed slurry. The fourth particle mixed slurry was milled 7 times to obtain the fourth particle slurry (D50 particle size = 250 nm). The fourth particle slurry was subjected to two-fluid spray drying to obtain the fourth particle raw material (D50 particle size = 8 nm). The fourth particle raw material was subjected to high-temperature sintering under nitrogen atmosphere at 780℃ for 8 hours to obtain the fourth particle sintered material. The fourth particle sintered material was subjected to vibratory sieving (through a 250-mesh sieve) to obtain the fourth particle (h4 = 0.002 μm, D4 = 5 μm, d4 = 4.996 μm).
[0215] 5) The first, second, third, and fourth particles obtained in steps 1-4 are mechanically mixed in a mass ratio of 0.1:0.6:0.2:0.1 to obtain lithium iron phosphate material. The lithium iron phosphate material, conductive agent (SP), and binder (PVDF) are mixed in a mass ratio of 97:0.5:2.5 to obtain the cathode material.
[0216] Steps 6-9 are basically the same as steps 4-7 in Example 1. In this example, a secondary battery 18 is obtained.
[0217] Comparative Example 1
[0218] This comparative example is basically the same as Example 1, except that the number of milling cycles in step 1 is adjusted to 19, the grading frequency to 70Hz, the first high-temperature sintering temperature to 680℃, and the sintering time to 7 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 730℃, the sintering time to 19 hours, the number of milling cycles in the second milling treatment is adjusted to 16, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:8. This comparative example yields a secondary battery 21.
[0219] Comparative Example 2
[0220] This comparative example is basically the same as Example 1, except that the number of milling cycles in step 1 is adjusted to 17, the grading frequency to 70Hz, the first high-temperature sintering temperature to 650℃, and the sintering time to 10 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 720℃, the sintering time to 14 hours, the number of milling cycles in the second milling treatment is adjusted to 13, and the mass ratio of the second granulated iron phosphate to sucrose is 1000:4. This comparative example yields secondary battery 22.
[0221] Comparative Example 3
[0222] This comparative example is basically the same as Example 1, except that the number of milling cycles in step 1 is adjusted to 7, the grading frequency to 60Hz, the first high-temperature sintering temperature to 670℃, and the sintering time to 11 hours. In step 2, the temperature of the second high-temperature sintering treatment is adjusted to 770℃, the sintering time to 4 hours, and the number of milling cycles in the second milling treatment is adjusted to 18. This comparative example yields a secondary battery 23.
[0223] Experimental Example 1
[0224] The following tests were performed on all embodiments and comparative examples, and the results are shown in Table 1.
[0225] 1. Particle size test
[0226] 1) Pretreatment: Discharge the battery to the lower limit voltage (2.5V) at 0.33C. Take the electrode sheet of the lithium-ion battery in the empty state and soak it in dimethyl carbonate (DMC) solution at room temperature for 4 hours. After soaking, take out the electrode sheet and dry it in a vacuum environment. Use a ceramic knife to scrape off the active material powder on the surface of the electrode sheet.
[0227] 2) SEM Testing: A layer of conductive adhesive was first applied to the sample holder, and the sample powder was then adhered to the sample holder. CP argon ion polishing was performed, followed by the deposition of a conductive film. The tools and sample stage were wiped with anhydrous ethanol, and a certain amount of the sample to be tested was placed on the sample stage. Observation was performed under a scanning electron microscope (SEM). The magnification was adjusted using the SEM for testing and imaging. The first and third particles were imaged at 20kx, and the second and fourth particles were imaged at 4kx.
[0228] 3) The size of the SEM images of the first to fourth particles and the negative electrode particles was measured using graphic statistical software. The particle size was collected using the diagonal line method, and five different non-overlapping areas were selected (to avoid local area deviation). One clear SEM image was taken for each area. Edges and agglomerated areas were avoided to ensure that the particles in the image are independently dispersed and without obvious overlap.
[0229] ;
[0230] .
[0231] Among them, f i The average particle size of a single non-overlapping region, i ranges from 1 to 5, corresponding to 5 SEM images; x is the particle number within a single SEM image, ranging from 30 to 100; N ix N represents the particle size value of a single non-overlapping region. 总x The number of particles collected in a single non-overlapping region.
[0232] 2. Primary and secondary particle quantity test
[0233] 1) Pretreatment: Discharge the battery to the lower limit voltage (2.5V) at 0.33C, take the empty electrode sheet, soak it in dimethyl carbonate (DMC) solution at room temperature for 4 hours, after soaking, take out the electrode sheet and dry it in a vacuum environment, and scrape the active material powder on the surface of the electrode sheet with a ceramic knife.
[0234] 2) Spread the scraped active material powder evenly on the conductive adhesive, place it directly into the SEM, select an SEM image with a suitable magnification and clear image, measure the particle size value of the particles using particle size measurement software (measure 400 particles), confirm the quantity of the two types of particles according to the distribution range of primary and secondary particles, and record the ratio of the number of primary particles to secondary particles as S.
[0235] 3. Carbon coating thickness test
[0236] 1) Pretreatment: Discharge the secondary battery to 2.5V at 0.33C, take the positive electrode sheet of the secondary battery in the empty state, soak it in dimethyl carbonate (DMC) solution at room temperature for 4 hours, after soaking, take out the positive electrode sheet and dry it in a vacuum environment, and scrape the active material powder on the surface of the positive electrode sheet with a ceramic knife.
[0237] 2) Add deionized water to the active material powder, add 0.1 wt% sodium dodecyl sulfate (SDS) as a dispersant, and disperse under low power ultrasonication for 10 minutes in an ice bath. Then centrifuge at 3000 rpm for 5 minutes, remove the supernatant, and repeat the above steps 5 times to obtain the analyte precipitate.
[0238] 3) The analyte was precipitated and vacuum dried at 60°C for 12 hours to obtain an active material powder sample.
[0239] 2) Take 1 mg of active material powder sample and place it in a sample tube. Add anhydrous ethanol and sonicate for 40 min. Use a pipette to take a small amount of solution and drop it onto a copper grid. Finally, dry the sample completely in a vacuum drying oven. Place the sample on the test stage and transfer it to the cavity. Use a transmission electron microscope (TEM). For different coating thicknesses, the thickness of the carbon coating needs to be measured at a suitable high magnification. Select 5 regions for measurement and take the average value.
[0240] 4. Powder resistivity test
[0241] The resistivity of the cathode material powder was measured using a four-probe powder resistivity meter. The specific steps were as follows: 0.7g of cathode material was weighed, the four-probe powder resistivity meter was set, the cathode material was placed in the material chamber, and the pressure was increased to 10 MPa. The resistivity value of the sample was then read from the device display. Unit: Ω·cm.
[0242] Table 1 Structural parameters of secondary batteries
[0243]
[0244] Experimental Example 2
[0245] The secondary batteries of all embodiments and comparative examples were subjected to the following tests, and the results are shown in Table 2.
[0246] 1. Energy density detection
[0247] The weight of the battery is measured and recorded as m (unit: kg). The battery is placed in a fixture, and a force of 3000 N is applied. It is charged at a constant current of 0.33 C to the upper limit voltage of 3.65 V, then left to rest for 30 minutes. It is then discharged at a constant current of 0.33 C to the lower limit voltage of 2.5 V, and left to rest for 30 minutes. This cycle is repeated three times to obtain the discharge capacity (unit: Ah) and the energy E (the average of the three cycles, unit: Wh). The discharge energy density is calculated using the formula: Discharge Energy Density = E / m, and the unit: Wh / kg.
[0248] 2. Dynamic performance testing
[0249] Place the battery in a 25°C environment and let it stand for 4 hours until it reaches thermal equilibrium. Charge the battery at a constant current of 0.33C to the upper limit voltage of 3.65V, then charge it at a constant voltage to the cutoff current of 0.05C; then discharge it at a constant current of 0.33C to the lower limit voltage of 2.5V. This constitutes one cycle. Perform 3 charge-discharge cycles, which are considered 3 standard cycles. Use the discharge capacity of the 3rd cycle as the standard capacity C of the battery.
[0250] The battery was charged to 50% SOC at a discharge rate of 0.33C; it was then discharged at a current of 1C for 18 seconds. The battery voltage U2 and current I before the discharge stopped and the battery voltage U1 after the voltage stabilized were recorded. The DC internal resistance R1 was calculated using the formula R1=(U2-U1) / I, with the unit being mΩ.
[0251] Table 2 Electrochemical performance parameters of secondary batteries
[0252]
[0253] As can be seen from Tables 1 and 2, the secondary battery prepared using the cathode material of this invention exhibits synergistic optimization of kinetic performance and energy density. The cathode material of this invention can be widely used in various fields with stringent requirements for battery performance.
[0254] Wherein, in the positive electrode materials of Examples 1 to 20, both the first particles and the second particles satisfy 1 < h1 / h2 ≤ 15, with D1 being 0.02 to 0.1 μm and D2 being 1 to 4 μm, so that uniform lithium ion transmission paths are formed in lithium iron phosphate, the internal impedance is reduced, and thereby the dynamic performance of the battery is improved; meanwhile, the first particles and the second particles with different sizes form a secondary close-packed structure, which improves the compaction density of lithium iron phosphate and significantly optimizes the energy density of the battery.
[0255] A comparison of Examples 1 to 9 shows that when the value of h1 / h2 is in the range of 1.4 to 3.3, the dynamic performance and energy density of the battery achieve a better balance. Wherein, when h1 satisfies 0.004 to 0.01 and h2 satisfies 0.003 to 0.007, the internal compaction and ion transmission kinetics of the positive electrode material are further optimized, so that the comprehensive performance of the battery is further improved.
[0256] An analysis of Comparative Examples 1 to 3 shows that when h1 = h2, or even h1 < h2, the ion transmission kinetics of the lithium iron phosphate material deteriorates, and the direct current internal resistance R1 of the battery increases significantly; while when h1 is much larger than h2, the packing structure in the lithium iron phosphate material deteriorates, and the energy density of the battery decreases significantly.
[0257] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, not to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that they can still modify the technical solution recorded in the foregoing embodiments, or equivalently replace some or all of the technical features thereof; and such modifications or substitutions do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of the embodiments of the present invention.
Claims
1. A positive electrode material, characterized in that, The cathode material includes lithium iron phosphate, which includes a first particle and a second particle. The first particle has a particle size of D1, which is 0.02~0.1μm, and the second particle has a particle size of D2, which is 1~4μm. The first particle includes a first lithium iron phosphate matrix and a first carbon coating layer disposed on at least a portion of the surface of the first lithium iron phosphate matrix, wherein the thickness of the first carbon coating layer is h1, and h1 is 0.0025~0.025μm; The second particle includes a second lithium iron phosphate matrix and a second carbon coating layer disposed on at least a portion of the surface of the second lithium iron phosphate matrix, wherein the thickness of the second carbon coating layer is h2, and h2 is 0.001~0.015μm; The cathode material satisfies: 1 <h1 / h2≤15。 2. The cathode material according to claim 1, characterized in that, The value range of h1 / h2 is 1.4 to 3.
3.
3. The cathode material according to claim 1, characterized in that, The value of h1 ranges from 0.004 to 0.01 μm; and / or, The value of h2 ranges from 0.003 to 0.007 μm.
4. The cathode material according to claim 1, characterized in that, The average diameter of the first lithium iron phosphate matrix is d1, and the value of d1 ranges from 0.01 to 0.092 μm; and / or, The average diameter of the second lithium iron phosphate matrix is d2, and the value of d2 ranges from 0.984 to 3.998 μm.
5. The positive electrode material according to claim 4, characterized in that, a = d2 - d1, b = h1 - h2; n = a × b, where the value of n ranges from 0.0019 to 0.
055.
6. The cathode material according to claim 5, characterized in that, The value of n ranges from 0.0024 to 0.0243.
7. The cathode material according to claim 5, characterized in that, The value of 'a' ranges from 0.9 to 3.8 μm; and / or, The value of b ranges from 0.001 to 0.015 μm.
8. The positive electrode material according to claim 1, characterized in that, The mass ratio of the first particle to the second particle is (0.5~4.99):(5~9.99).
9. The cathode material according to any one of claims 1-8, characterized in that, The lithium iron phosphate also includes a third particle, which includes a third lithium iron phosphate matrix and a third carbon coating layer disposed on at least a portion of the surface of the third lithium iron phosphate matrix. The particle size of the third particle is D3, and the value of D3 ranges from 0.12 to 0.8 μm; The thickness of the third carbon coating layer is h3,1 <h1 / h3≤12。 10. The cathode material according to claim 9, characterized in that, The value of h3 ranges from 0.002 to 0.02 μm.
11. The cathode material according to claim 9, characterized in that, The mass ratio of the first particle, the second particle, and the third particle is (0.001~0.2):(0.5~0.999):(0.2~0.3).
12. The cathode material according to claim 9, characterized in that, h2 <h3<h1。 13. The cathode material according to any one of claims 10-12, characterized in that, The lithium iron phosphate also includes a fourth particle, which includes a fourth lithium iron phosphate matrix and a fourth carbon coating layer disposed on at least a portion of the surface of the fourth lithium iron phosphate matrix. The fourth particle has a particle size of D4, and the value of D4 ranges from 4 to 35 μm. The thickness of the fourth carbon coating layer is h4,1 <h1 / h4≤20。 14. The cathode material according to claim 13, characterized in that, The value of h4 ranges from 0.001 to 0.015 μm.
15. The cathode material according to claim 13, characterized in that, The mass ratio of the first particle, the second particle, the third particle, and the fourth particle is (0.001~0.1):(0.5~0.9):(0.25~0.499):(0.001~0.15).
16. The cathode material according to any one of claims 1-8, 10-12, and 14-15, characterized in that, The powder conductivity of the positive electrode material is 2~500 Ω·cm.
17. A positive electrode plate, characterized in that, The positive electrode sheet comprises the positive electrode material according to any one of claims 1-16; the porosity of the positive electrode sheet is 10% to 40%.
18. A secondary battery, characterized in that, The secondary battery includes the positive electrode sheet as described in claim 17.
19. The secondary battery according to claim 18, characterized in that, The secondary battery also includes a negative electrode sheet, which comprises a negative electrode material, and the average particle size of the negative electrode material is 5~20μm.
20. The secondary battery according to claim 19, characterized in that, The negative electrode material includes graphite material, which comprises primary particles and secondary particles; The ratio of the number of primary particles to the number of secondary particles is 0.01 to 5.
21. The secondary battery according to any one of claims 18-20, characterized in that, The secondary battery also includes an electrolyte with an ionic conductivity of 2~30 mS / cm.
22. The secondary battery according to claim 21, characterized in that, The electrolyte includes a solvent, which includes a carboxylic acid ester; the carboxylic acid ester has a mass percentage content of 5 wt% to 30 wt% based on the mass of the solvent.
23. The secondary battery according to claim 22, characterized in that, The solvent also includes carbonates, wherein the number of carbon atoms in a single molecule of the carbonate is 3 to 5.
24. An electrical appliance, characterized in that, The secondary battery includes any one of claims 18-23.